2012
DOI: 10.1074/jbc.m111.304279
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of Chlamydomonas reinhardtii to Different Growth Irradiances

Abstract: Background: Photosynthetic organisms deal with different irradiance conditions. Results: In Chlamydomonas reinhardtii, acclimation to different irradiances of growth involves modulation of photosynthetic protein content per cell. Growth in high light induces activation of photoprotective mechanisms. Conclusion: Higher plants and green algae have evolved different acclimatizing mechanisms. Significance: Investigation of light-dependent modulation of photosynthetic proteins is crucial for directing optimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
169
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(201 citation statements)
references
References 80 publications
30
169
2
Order By: Relevance
“…The gene expression of different LHCs has been reported to be affected by light acclimation (Teramoto et al, 2002;Durnford et al, 2003;Yamano et al, 2008) and to be NAB1 regulated (Mussgnug et al, 2005). It has been observed that longterm high-light exposure of C. reinhardtii cells leads to a 50% decrease of Chl content (Neale and Melis, 1986;Bonente et al, 2012) and to changes in Chl-to-Car ratio (Niyogi et al, 1997a;Baroli et al, 2003;Bonente et al, 2012), suggesting reduction of the antenna size (Neale and Melis, 1986), although, in a more recent report , it was concluded that the antenna size is not modulated by light in this alga. Recently, a dependence of the antenna components on the carbon availability also was reported.…”
mentioning
confidence: 99%
“…The gene expression of different LHCs has been reported to be affected by light acclimation (Teramoto et al, 2002;Durnford et al, 2003;Yamano et al, 2008) and to be NAB1 regulated (Mussgnug et al, 2005). It has been observed that longterm high-light exposure of C. reinhardtii cells leads to a 50% decrease of Chl content (Neale and Melis, 1986;Bonente et al, 2012) and to changes in Chl-to-Car ratio (Niyogi et al, 1997a;Baroli et al, 2003;Bonente et al, 2012), suggesting reduction of the antenna size (Neale and Melis, 1986), although, in a more recent report , it was concluded that the antenna size is not modulated by light in this alga. Recently, a dependence of the antenna components on the carbon availability also was reported.…”
mentioning
confidence: 99%
“…In C. reinhardtii, Bonente et al (2012) showed that CEF is up-regulated under low or moderate light conditions, relative to high light. Importantly, mutants devoid of either NDH or pgr5 (Kono et al, 2014) were found to be lethal under fluctuating light conditions compared to wild-type, suggesting that both CEF pathways are critical under frequent dark to light transitions which should include cells cycling between light and dark zones in high density cultures.…”
Section: Cyclic Electron Flows (Cef) and The Role Of Proton Gradient mentioning
confidence: 99%
“…Under steady state light, Bonente et al (2012) reported high light acclimation of C. reinhardtii led to a nearly 3-fold reduction in chlorophyll compared to low light treated cells, but a concomitant accumulation of relatively high amounts of zeaxanthin and lutein involved in photoprotection. The authors found the average antenna size of both photosystem I and II was, in fact, not modulated by acclimation; rather, the regulation affected the PSI : PSII ratio.…”
Section: Photoacclimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Microalgae have been reported to radically increase their NPQ capacity even at moderate light intensities (Bonente et al 2012, Cazzaniga et al 2014 2014), though in one study, it was shown that the total contribution of these screening pigments to total NPQ was limited (Masojídek et al 1999). We did not measure a relative change in the absorption spectrum after a transfer from high light to mass culture.…”
Section: Possible Explanations For the Discrepancy Between The Model mentioning
confidence: 99%